Peran Digitalisasi dalam Efisiensi Operasional dan Strategi Penjualan: Studi Kasus PT Tunas Kreasi Digital (Looyal) dan Implikasinya pada Berbagai Sektor Usaha, Khususnya dalam Sektor Agribisnis - Mariana Adinata; Noor Rizkiyah (Jurnal Riset Multidisiplin Agrisosco, 2026)
Digital transformation has become a crucial factor in enhancing corporate competitiveness in the modern business era. This study aimed to analyze the role of digitalization through PT Tunas Kreasi Digital's Looyal ecosystem platform in supporting operational efficiency and sales strategies. A descriptive qualitative approach was employed, with primary data collected through observation, interviews with three key informants consisting of the Senior Strategic Client Manager, Directore, and Human Resources Department (HRD) staff of PT Tunas Kreasi Digital, as well as documentation during the internship period from 9 February to 05 June 2026. Data were analyzed using Miles and Huberman's Interactive Analysis Model. The results showed that the implementation of Software as a Service (SaaS)-based services, namely Wooblazz, Woogigs, Wootix, and Soloosi, accelerated administrative processes, improved data management effectiveness, supported customer engagement, and simplified real-time business operational management. User evaluation data indicated that Wooblazz achieved the highest user satisfaction level (100%), while Wootix demonstrated high operational efficiency and user satisfaction levels of 95%. Furthermore, integrated digital systems helped improve service speed, minimize transaction recording errors, and support more accurate data-driven decision-making. These findings provide practical implications for agribusiness actors in adopting digital technologies to enhance operational efficiency, customer engagement, and business competitiveness